2016
DOI: 10.3346/jkms.2016.31.5.688
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Long Non-Coding RNA MALAT1 Promotes Apoptosis of Glioma Cells

Abstract: The metastasis-associated lung adenocarcinoma transcription 1 (MALAT1) is a highly conserved long non-coding RNA (lncRNA) gene. However, little is known about the pathological role of lncRNA MALAT1 in glioma. In the present study, we explored the expression level of lncRNA MALAT1 in primary glioma tissues as well as in U87 and U251 glioma cell lines. Using qRT-PCR, we found that the expression of lncRNA MALAT1 was significantly increased in glioma tissues compared with that of paracancerous tissues. Meanwhile,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…Emerging evidence has showed that MALAT1 is implicated in many cancers, including digestive system, gynecological, and urological cancers [12-14]. MALAT1 has also been associated with the clinical outcomes of glioma patients [15], and silencing of MALAT1 leads to the increase of glioma cell apoptosis [16]. It is known that MALAT1 functions as an oncogene partly through inducing EMT.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has showed that MALAT1 is implicated in many cancers, including digestive system, gynecological, and urological cancers [12-14]. MALAT1 has also been associated with the clinical outcomes of glioma patients [15], and silencing of MALAT1 leads to the increase of glioma cell apoptosis [16]. It is known that MALAT1 functions as an oncogene partly through inducing EMT.…”
Section: Introductionmentioning
confidence: 99%
“…A universal siRNA with no homology with mammalian gene sequence was used as negative control. Sequences were designed as follows: MALAT1, forward 5'-GGG CUU CUC UUA ACA UUU AUU-3', reverse 5'-UAA AUG UUA AGA GAA GCC CUU)-3' (50 nM) (27,28); SOX2OT, forward 5'-GGA GAU UGU GAC CUG GCU UTT-3', reverse 5'-AAG CCA GGU CAC AAU CUC CTT)-3' (50 nM) (29); ANRIL, forward 5'-GGU CAU CUC AUU GCU CUA UTT-3', reverse 5'-CCA GUA GAG UAA CGA GAU ATT)-3' (25 nM) (24,30); and universal siRNA negative control, forward 5'-UUC UCC GAA CGU GUC ACG UTT-3' and reverse 5'-ACG UGA CAC GUU CGG AGA ATT-3' (50 nM). Transfections were performed using Lipofectamine ® 2000 (Invitrogen; Thermo Fisher Scientific, Inc.) at room temperature for 25 min and at 37˚C in an incubator containing 5% CO 2 for 6 h. Plasmids were constructed and extracted in our laboratory and siRNAs were synthesized by Shanghai GenePharma Co., Ltd. (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…As NEAT2 (nuclear-enriched abundant transcript 2), also known as MALAT1 (metastasis-associated lung adenocarcinoma transcript 1), is a highly conserved lncRNA associated with the metastatic potential of tumor cells, Han et al (2016a) found that the knockdown of NEAT2 by RNA interference could promote the invasion and proliferation of glioma cells. Concomitantly, the apoptosis rate of the glioma cell lines is shown to dramatically increase ( Han et al, 2016a ; Xiang et al, 2016 ). Over all, these results indicate that an investigation into the abnormal expression profiles of lncRNAs may help in the understanding of oncogenesis and identify novel potential treatment targets in glioma research and therapy.…”
Section: Profile Of Lncrnas In Human Glioma Research and Therapymentioning
confidence: 99%